Mechanical Design of a Switched Reluctance Motor With Small Airgap Length - Alexander Forsyth; Sanjeev Ravichandran; Thisuri H. Indiketiya; Ashish Kumar Sahu; Sudesh V. Pathirannahalage; Batuhan S. Yilmaz; Brock Howey; Nir Vaks; Mohammad E. Abdollahi; Berker Bilgin (IEEE Access)
This paper presents the mechanical design of a 70 kW Switched Reluctance Motor prototype with a nominal airgap length of 0.4 mm with a relatively large stator outer diameter of 280 mm. It presents the mechanical design considerations and manufacturing tolerances that are vital for an electric motor to maintain component integrity and meet performance requirements. Multi-stage design of the mechanical components and fittings for the complete mechanical system are presented and justified with finite element analysis results. The radial and axial stack-up analysis are presented which account for the dimensional variations during the manufacturing of motor components. The assembly of the motor prototype is described, which demonstrates that the axial and radial alignment of the motor components are achieved while maintaining the small airgap length required. The motor assembly is then verified with static end-of-line tests, such as winding insulation and housing leakage tests. Additionally, experimental modal analysis of the housing assembly is performed to examine the influence of the winding, housing, and potting on its modal frequencies and damping characteristics.